Mere education : C.S. Lewis as teacher for our time - Pike, Mark A. (Cambridge : Lutterworth Press, 2013)
The word 'mere' is used in the title of this book in its Middle English sense as an adjective 'nothing less than, complete'. This book is about schooling for a fair and vibrant society; it is about an education of hope, education that completes a person. In 'The Magician's Nephew' (1955), the first in C.S. Lewis' Chronicles of Narnia series, Digory and Polly are dragged back through time into a world that is ""devoid of life and barren of vegetation"". Such a world is not a safe place for children and young people. When C.S. Lewis wrote that the task of the modern educator is 'to irrigate dese.
Part 1. The hinge of the wardrobe door : core values, character and Christianity -- part 2. The furniture of the house : schooling children -- part 3. Professor Lewis : cultural interpreter for educators -- part 4. The professor's house : leading on school ethos and excellence in teaching.
Includes bibliographical references and indexes.
Online resource; title from PDF title page (ebrary, viewed October 14, 2013).
Master record variable field(s) change: 072
Keywords: Lewis, C. S. -- 1898-1963.; Lewis, C. S. -- 1898-1963.; Literature -- Study and teaching; EDUCATION -- Essays; EDUCATION -- Organizations & Institutions; EDUCATION -- Reference; Literature -- Study and teaching; Lewis, C. S. -- (Clive Staples), -- 1898-1963.; Literature -- Study and teaching; RELIGION / Christian Education / Children & Youth; Electronic books